Metformin may be a viable adjunctive therapeutic option to potentially enhance immune reconstitution in HIV-positive immunological non-responders - Zaongo, Silvere D.; Chen, Yaokai (Chinese medical journal, 2023)
Incomplete immune reconstitution remains a global challenge for human immunodeficiency virus (HIV) treatment in the present era of potent antiretroviral therapy (ART), especially for those individuals referred to as immunological non-responders (INRs), who exhibit dramatically low CD4+ T-cell counts despite the use of effective antiretroviral therapy, with long-term inhibition of viral replication. In this review, we provide a critical overview of the concept of ART-treated HIV-positive immunological non-response, and also explain the known mechanisms which could potentially account for the emergence of immunological non-response in some HIV-infected individuals treated with appropriate and effective ART. We found that immune cell exhaustion, combined with chronic inflammation and the HIV-associated dysbiosis syndrome, may represent strategic aspects of the immune response that may be fundamental to incomplete immune recovery. Interestingly, we noted from the literature that metformin exhibits properties and characteristics that may potentially be useful to specifically target immune cell exhaustion, chronic inflammation, and HIV-associated gut dysbiosis syndrome, mechanisms which are now recognized for their critically important complicity in HIV disease-related incomplete immune recovery. In light of evidence discussed in this review, it can be seen that metformin may be of particularly favorable use if utilized as adjunctive treatment in INRs to potentially enhance immune reconstitution. The approach described herein may represent a promising area of therapeutic intervention, aiding in significantly reducing the risk of HIV disease progression and mortality in a particularly vulnerable subgroup of HIV-positive individuals.